1470 nm Diode Laser Enucleation vs Plasmakinetic Resection of the Prostate for Benign Prostatic Hyperplasia: A Randomized Study - Zhang, Jun (J Endourol, 2019)
Objective: The purpose of the current work was to comparatively assess 1470 nm diode laser enucleation of the prostate (DiLEP) and plasmakinetic resection of the prostate (PKRP) for treating benign prostatic hyperplasia (BPH). Patients and Methods: From January 2016 to March 2017, 157 individuals with bladder outflow obstruction caused by BPH were randomized to DiLEP and PKRP groups, for prospective analysis. Of these, 152 cases were evaluated before operation and at 3, 6, and 12 months postsurgery. Patient baseline properties, presurgery data, and postsurgical outcomes were comparatively assessed, as well as complications. Results: There were no significant preoperative differences between surgical groups. DiLEP-treated cases showed remarkable reduced operative time, postsurgical bladder irrigation time, catheterization duration, and hospital stay compared with the PKRP group (P < 0.001). Hemoglobin amount decrease was markedly less pronounced after DiLEP (P = 0.004). However, no patients needed blood transfusion in either group. The decrease in sodium level showed no marked differences between the DiLEP and PKRP groups (P = 0.380). In addition, complications were comparable and no significant differences in both groups. At 3, 6, and 12 months, International Prostate Symptom Score (IPSS), quality of life (QoL), maximum flow rate (Qmax), and postvoid residual (PVR) were similar in both groups (P > 0.05). Conclusions: DiLEP and PKRP are similar in efficacy and safety for relieving obstruction and low urinary tract symptoms. Compared with PKRP, DiLEP has decreased risk of hemorrhage, operative time, bladder irrigation time, catheterization duration, and hospital stay. However, IPSS, QoL, Qmax, and PVR were similar for both procedures within 12 postoperative months.